Coraline - Gaiman, Neil; McKean, Dave (Waterville, Me. : Thorndike Press, 2003)
Looking for excitement, Coraline ventures through a mysterious door into a world that is similar, yet disturbingly different from her own, where she must challenge a gruesome entity in order to save herself, her parents, and the souls of three others.
aReprint. Originally published: New York : HarperCollins, 2002.
Keywords: Large type books; Supernatural -- Fiction; Horror stories; Large type books